2020
DOI: 10.1007/s00420-020-01566-x
|View full text |Cite
|
Sign up to set email alerts
|

Working conditions as risk factors for early exit from work—in a cohort of 2351 employees in Germany

Abstract: Objectives We would assess the possible impact of a range of physical and psychosocial working conditions on early exit from paid employment (i.e., before retirement age) in a representative employee population in Germany. Methods We analysed a cohort from the German Study on Mental Health at Work (S-MGA) with a baseline of 2351 employees in 2011/12, sampled randomly from the register of integrated employment biographies (IEB) at the Institute for Employment Research (IAB). Follow-up ended mid-2015. Early Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 80 publications
(148 reference statements)
0
16
1
Order By: Relevance
“…Also, as our analyses concern the second wave of the study, the sample may have become biased by drop-out. Non-responder analyses have been conducted to look for differences between waves (d’Errico et al 2021 ). Its results showed that men and women equally often continued to the second study wave, but that younger as well as unskilled employees did not continue to the second wave as often as older persons, managers and professionals did.…”
Section: Discussionmentioning
confidence: 99%
“…Also, as our analyses concern the second wave of the study, the sample may have become biased by drop-out. Non-responder analyses have been conducted to look for differences between waves (d’Errico et al 2021 ). Its results showed that men and women equally often continued to the second study wave, but that younger as well as unskilled employees did not continue to the second wave as often as older persons, managers and professionals did.…”
Section: Discussionmentioning
confidence: 99%
“…However, musculoskeletal pain is common in the working population and the prevalence of pain increases with age [1]. More specifically, workers with physically demanding occupations are at a particularly high risk of both musculoskeletal pain [2,3], long-term sickness absence, and disability pension compared to workers within more sedentary occupations [4][5][6]. Granted that both age and physically demanding work are predictors of musculoskeletal pain, these factorsespecially in combinationconstitute significant risk factors for being unable to work until statutory pension age.…”
Section: Introductionmentioning
confidence: 99%
“…One is that a low response rate could have biased the results. However, based on a comparison between our sample and the population from which it was drawn, the bias due to regional characteristics, gender, age, education, profession and income was limited [ 28 , 54 ]. A second limitation is that the study does not cover employees younger than 30 years or those being civil servants or self-employed.…”
Section: Discussionmentioning
confidence: 99%